Fumio Kishida’s First Year in PM Office: Is Abenomics to End or Stay? - V. G. Shvydko (Russian Japanology Review)
The article addresses the experience of Fumio Kishida’s first year as Prime Minister of the Japanese government with respect to its economic policy vision and implementation. This policy is analyzed by comparing it to the policy pursued over the past ten years by PM Kishida’s predecessors in the office, on the one hand, and to the commitments he announced during the 2021 election campaign, on the other hand. The paper notes that, in its basic moments, the economic policy of the cabinet of the new leader of the ruling Liberal Democratic Party continues the course previously maintained by the team of then-PM Abe Shinzō, known as Abenomics. This is manifested in the specific use of basic instruments of macroeconomic policy, primarily in the monetary and tax areas, as well as in setting priorities for the policy to stimulate consumption and economic activity. Continuity of the course can be particularly illustrated by the soft monetary policy; a positive view of the depreciation of the Japanese national currency; the moderately expansionary fiscal policy relying on domestic borrowing; preference given to interests of the national corporate sector. Legacy inherited from the previous administrations also includes government measures to revitalize deferred private demand, promoting investment in R&D, venture, and innovative enterprises with a particular focus on regional economies. Kishida’s particular emphasis on invigorating redistributive mechanisms and increasing the share of wages in the total national income has not yet resulted in specific decisions and actions by the government. Kishida’s commitment to expand the number of beneficiaries of the capitalist market system as part of his idea of “new capitalism” is yet to be carried out. In recent months, the attention of the government and its economic team has largely been focused on overcoming the consequences of the disruption of transnational production, trade and logistics chains caused by the coronavirus pandemic and rising geopolitical tensions. In addressing this issue, the government prioritizes subsidizing businesses and households to partially offset energy and food price hikes, securing diversification or localization of critical links of trade and production chains, as well as the exclusion from them of politically undesirable or unstable locations. At this stage, however, the actions of the government are limited to setting relevant goals and plans to provide finance for programs with effectiveness yet to be proven.